(untitled) (Research, Society and Development, 2021)
Objective: To delineate the epidemiological profile of women positive for syphilis during pregnancy in the state of Sergipe in ten years. Method: Retrospective cross-sectional study conducted between 2010 and 2019. The data were obtained from DATASUS. All calculations were performed with Excel software from the database itself. The selected variables included were: syphilis infection in pregnancy, education, ethnicity, age group, and gestational age. Results: There was an increase in the number of syphilis cases in pregnant women from 2010 to 2019, with an increase of approximately 17.1% per year. It was found that 74.8% of cases occurring in brown women, 50.3% in women in the age group of 20 to 29 years old, 27% in women with an educational level of 5th to 8th grade incomplete, and 38% of cases were diagnosed in the third trimester of pregnancy. Conclusion: This study presented the growth of syphilis cases in pregnant women in the state of Sergipe in the last decade, predominantly in brown, young, and poorly educated women.